Analysis of Work Discipline and Work Motivation on Employee Job Satisfaction at the Regional Financial and Asset Management Agency of XYZ Province (Case Study on the Regional Property Management Division) - Arneta Putri Fatmawati; Khaerul Rizal Abdurahman (Transpublika Publisher, 2025)
The background of this study is the indication of suboptimal job satisfaction, as reflected in the high rate of employee tardiness, which is suspected to be caused by low employee discipline, as seen from the high rate of incomplete attendance, and low work motivation due to limited career paths and study assignment opportunities. Therefore, this study aims to analyze in-depth the influence of work discipline and work motivation on the job satisfaction of employees in the Regional Asset Management Division (BMD) of the BPKAD of XYZ Province. This study employs a qualitative approach with a case study method. Data were collected through in-depth interviews with four employees and one key managerial informant, non-participant observation, and document studies. Data were analyzed using data reduction, data presentation, and conclusion drawing, with data validity tested through triangulation. The results show that work discipline is considered good by the leadership; however, in practice, there are discrepancies due to time flexibility and administrative negligence, particularly regarding attendance and break times. Employee motivation varies significantly, polarizing between those who perceive a bright and clear career path and those who feel stagnant due to limited promotion opportunities. This perception directly affects job satisfaction. It can be concluded that both discipline and motivation significantly influence job satisfaction within the civil servant (ASN) environment.